ILLEGAL PARKING OF VEHICLES ON THE SIDEWALKS OF IN TEGAL CITY - Winta, Ananda Natasya; Brillianti , Dani F. (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
Illegal parking on sidewalks disrupts pedestrian mobility, increases traffic congestion, and undermines urban planning efforts. In the area of Tegal City, the issue of illegal parking has intensified, especially in high-traffic zones near commercial and tourist areas, creating significant challenges for city management and residents.This study aims to identify the main factors contributing to illegal parking on sidewalks in Tegal’s "Malioboro" area and to propose actionable recommendations for reducing the frequency of such parking behavior. A Likert scale questionnaire was used to assess respondents’ attitudes, motivations, and perceptions related to illegal parking. Statements within the questionnaire targeted factors such as the availability of legal parking spaces, parking fees, enforcement strictness, and accessibility preferences. The study surveyed a population of 100 respondents, including drivers and residents who frequently visit or commute within the area of Tegal City(.Findings indicate that limited availability of designated parking, high fees for legal parking, and low enforcement levels are the primary factors contributing to illegal parking on sidewalks. The results of this study indicate that there is a significant correlation between the driver’s comfort level and the frequency of illegal parking on the sidewalk, which shows that increasing driver comfort tends to be associated with a higher frequency of illegal parking on the sidewalk. The study recommends increasing legal parking facilities, adjusting parking fees, and improving law enforcement measures as effective strategies to address the issue. Educating the public on the impacts of illegal parking on pedestrian access and traffic flow is also advised.